B-cell epitope mapping and characterization of antibody responses to recombinant PvRipr in malaria-exposed individuals - Soares, Isabela Ferreira; Rodolphi, Cinthia Magalhães; Alencar, Ana Luiza Carneiro; Matos, Ada da Silva; Rodrigues-da-Silva, Rodrigo Nunes; Baptista, Barbara de Oliveira; Martorano, Rodrigo Medeiros; de Souza, Hugo Amorim dos Santos; Riccio, Evelyn Kety Pratt; de Barros, Jenifer Peixoto; Totino, Paulo Renato Rivas; Daniel-Ribeiro, Cláudio Tadeu; et al. (Frontiers in Immunology, 2026)
IntroductionMalaria caused by P. vivax continues to be a serious public health problem, especially in countries like Brazil where P. vivax accounts for more than 80% of diagnosed cases. Since this plasmodial species is characterized as one of the most difficult to eliminate, the development of a specific vaccine for P. vivax may be an essential tool for effective control of the disease. The protein Ripr has been described in P. falciparum as an essential part of the erythrocyte invasion complex. Given the limited number of P. vivax vaccine antigens currently under investigation, this study aimed to characterize, the naturally acquired humoral immune response to Ripr protein of P. vivax.MethodsELISA assays were performed using plasma samples from individuals naturally exposed to malaria in the Brazilian Amazon in order to determine levels of IgM, IgG and IgG subclasses against PvRipr. In addition, linear B-cell epitopes within the protein were identified.Results and DiscussionOur results demonstrated that PvRipr is naturally immunogenic, as more than 60% of the individuals presented IgM or IgG antibodies against recombinant PvRipr. The profile of IgG subclasses was also investigated and higher frequencies of seropositive individuals for IgG1 and IgG2 were observed. After in silico prediction, a total of four linear B cell epitopes were identified in PvRipr, from these sequences, B-PvRipr(879-888) and B-PvRipr(923-958) had higher frequencies of seropositive individuals and reactivity indexes in comparison to the other tested epitopes. Moreover, levels of IgG antibodies specific for these two epitopes were strongly correlated with the levels of IgG antibodies against recombinant PvRipr and especially with IgG3 antibodies, a cytophilic subclass widely cited in the protective immune response against malaria.